Historical, mathematical and nutritional bases of Pearson Square as a fit method for ruminant rations - Santana, A. A.; Pernía, L. A.; Santana, D. A. (Cuban Journal of Agricultural Science, 2016)
To analyze the historical evolution and the mathematical and nutritional bases of Pearson square, as fit method for ruminant rations, with the objective of proposing a faster and more professional substitute way, a documental research was performed and theoretical methods of research were also applied. It was possible to conclude that the method is old, simple in its procedure and, because of its mathematical basis, exact and adaptable to the rations formulation for ruminants, adjusting a nutrient and the dry matter required with two feeds, but it can be substituted by a simple equation stated at the end of the research, which allows to save time and steps with more professionalism. Key words: Pearson square, method, rations, formulations, equations.